2021
DOI: 10.1007/s11071-021-06471-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an artificial neural network and Gompertz model for predicting the dynamics of deaths from COVID-19 in México

Abstract: The present work is focused on modeling and predicting the cumulative number of deaths from COVID-19 in México by comparing an artificial neural network (ANN) with a Gompertz model applying multiple optimization algorithms for the estimation of coefficients and parameters, respectively. For the modeling process, the data published by the daily technical report COVID-19 in Mexico from March 19th to September 30th were used. The data published in the month of October were included to carry out the prediction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…Based on this, neural networks and deep learning are classical methods in the prediction field, and various scientists have tried to make predictions using different methodologies. Different neural network prediction methods or models are widely used in the prediction of COVID-19 events [18][19][20][21][22][23][24]. e deep learning methods have shown promise in healthcare prediction challenges involving electrocardiogram data [25].…”
Section: Main Forecasting Methods Andmentioning
confidence: 99%
“…Based on this, neural networks and deep learning are classical methods in the prediction field, and various scientists have tried to make predictions using different methodologies. Different neural network prediction methods or models are widely used in the prediction of COVID-19 events [18][19][20][21][22][23][24]. e deep learning methods have shown promise in healthcare prediction challenges involving electrocardiogram data [25].…”
Section: Main Forecasting Methods Andmentioning
confidence: 99%
“…An S Gompertz (SG) growth model was employed to model the damage growth. 37,38 According to the basal data, predicted values were obtained for the maximum damage (a = 1.0). A 90% confidence interval and 90% prediction interval were also determined.…”
Section: Numerical Prediction Of Shalementioning
confidence: 99%
“… 10 Ünlü and Namlı [ 24 ] Predicting COVID-19 confirmed cases and deaths in seven countries Confirmed cases Deaths Applying e Support Vector Machines (SVM), Holt-Winters, Facebook's Prophet, and Long-Short Term Memory (LSTM) for forecasting Using only RMSE in the interpretation of results 11 Niazkar and Niazkar [ 25 ] Estimating the confirmed cases of COVID-19 in China, Japan, Singapore, Iran, Italy, South Africa, and the United States of America. Chronological data of confirmed and death cases Applying fourteen ANN-based models to predict the COVID-19 outbreak Using a limited number of data 12 Hamadneh et al [ 26 ] Forecasting the number of total confirmed cases, total recovered cases, and total deaths in Brazil and Mexico The requested data Using ANN to estimate the number of cases of COVID-19 with prey predator algorithm (PPA) There is no comparative analysis to compare the results 13 Toga et al [ 27 ] Predicting the infected cases, the number of deaths, and the recovered cases with ARIMA and ANN in Turkey Susceptible cases Days Curfews Laboratory tests Determining the susceptible case number for each day after the first recovered case 14 Kumari and Toshniwal [ 28 ] Forecasting the COVID-19 outbreak in India with ANN Cumulative confirmed, new, and cumulative deceased cases recorded daily Utilizing a mathematical curve fitting model to understand the performance of the proposed model Not conducting a comparative analysis 15 Conde-Gutiérrez et al [ 29 ] Estimating the cumulative number of deaths from COVID-19 in México Cumulative number of deaths Comparing ANN with Gompertz model in estimating the number of deaths 16 …”
Section: Related Workmentioning
confidence: 99%